Breast Implant-Associated Anaplastic Large Cell Lymphoma - P. L. Moori; F. Ibison; D. Jacob; J. Iddon (Hindawi Limited, 2020)
Breast implant-associated anaplastic large cell lymphoma (BIA-ALCL) is a rare, non-Hodgkin lymphoma which arises within the capsules of breast implants. These particular tumours have expression of CD30 and are negative for Anaplastic Lymphoma Kinase (ALK). Here, we report a case of BIA-ALCL in a 48-year-old woman post breast reconstruction. This case report is aimed at raising awareness and education on the significance of considering the development of BIA-ALCL in cases where cytology is negative and helping better understand this disease process.